2022
DOI: 10.1155/2022/4948943
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Clinical Characteristics and Risk Factors of Postoperative Recurrence and Malignant Transformation of Low-Grade Glioma

Abstract: This research was developed to explore the clinical characteristics and related risk factors of postoperative recurrence and malignant transformation of low-grade glioma (LGG). The subjects were rolled into observation group (19 cases) and control group (51 cases) according to recurrence and malignant transformation during the follow-up period. The clinical data of the two groups were compared, and the risk factors of recurrence and malignant transformation were analyzed with the time of recurrence and maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…LGG subtype. Despite the heterogeneity among LGG subgroups [2][3][4], more than half of LGG patients will experience malignant transformation, leading to poor prognosis [5]. To address such issue and classify LGG more accurately, the diagnostic criteria of LGG were revised in the latest WHO classi cation in 2021, which emphasizes the role of molecular markers [6].…”
Section: Introductionmentioning
confidence: 99%
“…LGG subtype. Despite the heterogeneity among LGG subgroups [2][3][4], more than half of LGG patients will experience malignant transformation, leading to poor prognosis [5]. To address such issue and classify LGG more accurately, the diagnostic criteria of LGG were revised in the latest WHO classi cation in 2021, which emphasizes the role of molecular markers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Grade II gliomas are often invasive growths that exhibit minimal proliferative activity as well as a low level of malignancy. Nevertheless, if the extent of resection is inadequate, remaining lesions will return and even grow into high-grade lesions, thereby threatening the patient’s life [ 4 , 5 , 6 ]. In addition, although the surgical prognosis for individuals with an LGG is favorable, malignant transformation occurs in certain patients, which later refers to the evolution of an LGG to a high-grade glioma (HGG) (WHO grade III or grade IV tumor) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%